Was diese Frau so alles treibt - Jewison, Norman; Metty, Russell; Day, Doris; Garner, James; Francis, Arlene (Doris Day: 4-Movie Collection, 2021)
In the latter part of Doris Day's movie career where she ventured into romantic comedies she generally played one of two stereotypes, the loving wife and mother or the head strong, feisty career woman. Occasionally these two different characters crossed over which was the case with "The Thrill of It All" the first of the two movies which Doris Day made with James Garner, the second "Move Over, Darling" being released in the same year. And as you would expect from a Doris Day romantic comedy "The Thrill of It All" has all those components which made her movies so much fun from the facial humour, the set piece gags and the romance ... What this all boils down to is that whilst "The Thrill of It All" is dated with its comedy around 60s ideal and stereotypes it's still great fun. There is a witty cleverness to much of the humour and although it is predictable when it comes to the storyline the performances of Doris Day and James Garner make it work. [www.themoviescene.co.uk]